Funkcja personalna (na tle nauk o zarządzaniu) a uwarunkowania metodologiczno-paradygmatyczne nauk społecznych - Antczak, Zbigniew (Personnel Function (Human Capital, Human Resources Management) in the Management Science on the Methodological-Paradigmatic, 2008)
The results presented in the paper come from the autor's scientific diagnosis of the influence the methodological-paradigms conditioned by personnel function (HC, Human Capital; HRM, Human Resources Management) in enetrprises functioning in Polish condditions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 23-35